2002
DOI: 10.1080/14634980290031848
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of metals in the East Calcutta wetland ecosystem

Abstract: This study was initiated to examine the extent of toxic metal contamination of the east Calcutta wetland ecosystem. Biological oxygen demand, chemical oxygen demand, total dissolved solids, conductivity, total suspended solids, total hardness, and pH were recorded from six different locations on the sewage carrying canals including an industrial effluent-fed fish pond in the eastern Calcutta (lat. 22°33´-22°40´ N; long. 88°25´-88°35´ E). Concentrations of metals such as Pb, Cu, Cr, Zn, Fe, Mg, and Mn in wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…For comparison, twelve (six of each species) "uncontaminated" (uncontaminated from industrial wastes), control samples were also collected from two natural fishponds at Panduah, West Bengal, India (about 85 km north of the contaminated sampling sites) along with bottom sediment and water. Selection of elements for the study was carried out according to the major constituting elements that contaminate the concerned area as per the previous reports (Chattopadhyay et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, twelve (six of each species) "uncontaminated" (uncontaminated from industrial wastes), control samples were also collected from two natural fishponds at Panduah, West Bengal, India (about 85 km north of the contaminated sampling sites) along with bottom sediment and water. Selection of elements for the study was carried out according to the major constituting elements that contaminate the concerned area as per the previous reports (Chattopadhyay et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The huge amounts of composite, heavy-metal-contaminated effluents (nearly 50 000 m 3 · d -1 ) that flow down through a web of canals into the wetlands are also utilized by local farmers in pisciculture. Nearly 10 915 metric tons of fish were produced annually in 286 large wastewater fed fishponds (Bheris), over 30% of total wetland area (Chattopadhyay et al 2002). Among several cultivated species of fish, Nile tilapia, Oreochromis niloticus L., and Mozambique tilapia, O. mossambicus (Peters, 1852), are familiar for their high fecundity and fast growth rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in information technology based data retrieval system allowed prediction of the putative functions of the different groups of microbes indicating the possible presence of metal accumulating, oil degrading, antimicrobial compound producing as well as enzyme producing bacteria which can be exploited for commercial purposes . The removal of metals from waste water during its journey through the wetland (Chattopadhyay et al, 2002) and the presence of metal accumulating microbes from EKW have been reported in a variety of studies (Adarsh et al, 2007;Chowdhury et al, 2008).…”
Section: Microbial Diversity and Commercial Potentialmentioning
confidence: 99%
“…One reason for the purification of sewage is the abundant quantity of algal photosynthetic oxygen generated in the pond. Bheri causes detoxification of waste water by reducing heavy metals up to 25-99% (Chattopadhyay et al, 2002), while maintaining the biological oxygen demand at above 80% (http://www.ecotippingpoints.org/indepth/indiawetlands .html). The shallow pond allows sunlight to penetrate to its bottom and thereby helps in photosynthesis.…”
Section: Geographical Location and The Traditional Practicementioning
confidence: 99%